On the Role of the Environments and Star Formation for Quasar Activity - Bettoni, Daniela; Falomo, Renato; Kotilainen, Jari K.; Karhunen, Kalle (Frontiers in Astronomy and Space Sciences, 2017)
We investigate the host galaxy and environment properties of a sample of 400 low z (<0.5) quasars that were imaged in the SDSS Stripe82. We can detect and study the properties of the host galaxy for more than 75% of the data sample. We discover that quasar are mainly hosted in luminous galaxies of absolute magnitude M* − 3 < M(R) < M*1 and that in the quasar environments the galaxy number density is comparable to that of inactive galaxies of similar luminosities. For these quasars we undertake also a study in u,g,r,i, and z SDSS bands and again we discover that the mean colors of the quasar host galaxy it is not very different with respect to the values of the sample of inactive galaxies. For a subsample of low z sources the imaging study is complemented by spectroscopy of quasar hosts and of close companion galaxies. This study suggests that the supply and cause of the nuclear activity depends only weakly on the local environment of quasars. Contrary to past suggestions, for low redshift quasar there is a very modest connection between recent star formation and the nuclear activity.